Life after a cluster intervention: Insights from shrimp farming in Bangladesh - Narayanan, Sudha; Sakil, Abdul Zabbar; Kabir, Razin; Redoy, Md.; Belton, Ben (International Food Policy Research Institute, 2025)
This project note summarizes insights from a three-year research project focused on an ambitious cluster intervention by the Department of Fisheries (DoF), Government of Bangladesh for shrimp farmers. In 2022, as part of a World Bank funded project, the Department of Fisheries organized smallholder shrimp farmers with contiguous ponds into clusters in Khulna, Satkhira and Bagerhat districts in southwest Bangladesh. Each cluster brought together 20-25 farmers, with pond sizes of at most 1.5 acres in size, to deliver training on best management practices, supply inputs, and encourage coordination. Group members were encouraged to follow a suite of management practices aimed at raising farm productivity, reducing the incidence of shrimp disease, and increasing the supply of raw material for processors. These measures included farming bagda shrimp (P. monodon)—Bangladesh’s main export species—in monoculture, raising shrimp stocking densities, stocking disease-free shrimp larvae (SPFPL), using factory-made feeds, deepening ponds, erecting biosecurity fencing, and coordinating stocking and harvesting activities with other group members. The costs of deepening ponds and adopting other improved management practices were borne by farmers themselves, but the clusters that made these investments received free SPF-PL and feed as incentives for doing so. The goal of this cluster intervention was to promote sufficient volumes of shrimp for processing plants for export, eventually paving the way for instituting traceability systems and group-based sustainability certification, increasingly a requirement in global retail markets. Even at the time of inception, the cluster program was intended as a time-bound two-year project that would end in 2025.